The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-89102008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Validade de indicadores do consumo de alimentos e bebidas obtidos por inquérito telefônico

Abstract: OBJECTIVE:To evaluate the reproducibility and validity of data on food and beverage intake obtained by means of a telephone-based surveillance system. METHODS:Reproducibility and validity analyses were carried out in two random subsamples (n=112 and n=119, respectively) of the total sample (N=2,024) of adults (≥18 years) studied by the system in 2005 in the municipality of São Paulo, Southeastern Brazil. Indicators evaluated included protective factors (daily or almost daily intake of fruit and vegetables) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
25

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 12 publications
2
38
0
25
Order By: Relevance
“…Monteiro et al 26 demonstrated good reproducibility and adequate validation for most of the questions in the eating analysis of VIGITEL; thus, the non recovery of a sole healthy eating construct is not a result of information bias.…”
Section: Discussionmentioning
confidence: 99%
“…Monteiro et al 26 demonstrated good reproducibility and adequate validation for most of the questions in the eating analysis of VIGITEL; thus, the non recovery of a sole healthy eating construct is not a result of information bias.…”
Section: Discussionmentioning
confidence: 99%
“…The present article describes the results pertaining to indicators of physical activity and sedentariness. The reliability and validity of diet-related indicators was described in Monteiro et al 9 …”
Section: Introductionmentioning
confidence: 99%
“…A validade de estimativas de prevalências de fatores de risco de doenças e agravos crônicos não transmissíveis obtidas por meio do inquérito telefônico VIGITEL tem sido demonstrada 18,19 . Destaca-se que a pesquisa em Botucatu apresentou elevada proporção de entrevistas completadas em relação ao total de indivíduos sorteados (86,9%), ligeiramente superior à observada em São Paulo (84,7%) 15 .…”
Section: Discussionunclassified